The Socioemotional Costs and Benefits of Social-Evaluative Concerns: Do Girls Care Too Much? - Rudolph, Karen D. (2005)
This research investigated the hypothesis that girls’ heightened concerns about social evaluation contribute to sex differences in depression and interpersonal competence during early adolescence. A short-term longitudinal study was conducted with 474 adolescents to examine the consequences of heightened social-evaluative concerns. Adolescents reported on their levels of social-evaluative concerns and depressive symptoms. Teachers provided ratings of adolescents’ competence with peers (displays of prosocial and aggressive behavior). As anticipated, girls demonstrated higher levels of social-evaluative concerns, depressive symptoms, and interpersonal competence than did boys. Moreover, path analysis confirmed that heightened social-evaluative concerns were associated both concurrently and over time with higher levels of depression, as well as with higher levels of interpersonal competence. Notably, social-evaluative concerns accounted fully for the sex difference in depression and partially for the sex difference in interpersonal competence. These findings highlight the need to consider both the socioemotional costs and benefits of sex-linked relational orientations.